Hubungan Lama dan Posisi Duduk dengan Kejadian Low Back Pain (LBP) pada Mahasiswa di Fakultas Kedokteran Universitas Muslim Indonesia Angkatan 2019 - Nurul Annisa Amin; Achmad Harun Muchsin; Nur Fadhillah Khalid; Andi Dhedie Prasatia Sam; Rahmawati (Universitas Muslim Indonesia, 2023)
Low back pain (LBP) is pain that is felt in the lower back due to various reasons. The sitting position is a good position in carrying out activities such as studying, especially when attending lectures. Medical students are very synonymous with lecture activities in a sitting position for a long time. To determine the relationship between sitting position and sitting duration with the incidence of low back pain in students of the Faculty of Medicine, Indonesian Muslim University class of 2019. This research is an observational analytic study with a cross-sectional approach using a total sampling method of 154 subjects. Based on the results of the analysis of the relationship between sitting position and the incidence of low back pain, it can be seen that the p value = 0.004 obtained the results of 95 people (61.7%) who experienced a reclining sitting position and based on the results of the analysis of long sitting with the incidence of low back pain, it can be seen that the value p value = 0.040 results obtained as many as 91 subjects (59.1%) who sat for > 4 hours. There is a relationship between length of time and sitting position with the incidence of low back pain in students of the Faculty of Medicine, Indonesian Muslim University Class of 2019